Kearifan Lokal Masyarakat Etnik Jawa Dalam Interaksi Sosial Keagamaan Di Desa Kuta Baru Kecamatan Tebing Tinggi Kabupaten Serdang Bedagai - Windari, Yulia; Putra, Ilham Mirzaya (Jayapangus Press, 2025)
Local wisdom reflects the unique culture of an area which includes socio-religious interactions, relationships with the environment, and belief systems. The aim of this research is to describe the local wisdom of the Javanese ethnic community in Kuta Baru Village, understand the cultural meaning and socio-religious values of this tradition, and reveal the community's strategy in preserving local wisdom in the midst of modernization and globalization. This research uses a qualitative approach and descriptive research type. The data collection method is through observation and in-depth interviews with 5 informants. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, and the validity of the data was tested by triangulation. The results show that tangible (Tangible) local wisdom in Kuta Baru Village is in the form of mutual cooperation (rewang), kenduri, tingkeban, traditional ceremonies of temu manten, among-among, punggahan, pintan installation, and intangible local wisdom (Intangible), in the form of Javanese, is used in daily communication and traditional ceremonies. Traditions that contain socio-religious values include kenduri, among-among, punggahan, and tingkeban. Its preservation is carried out through education, training, and teaching language and culture to the younger generation. The implications of this research emphasize the important role of local wisdom of the Javanese community in Kuta Baru Village in strengthening socio-religious interactions and maintaining cultural identity amidst modernization. The results can be a reference for the government, educational institutions and society in preserving culture as well as a reference for further research on social harmony and cultural sustainability.